Analysis Juridical Restoration of Justice Against Perpetrator follow Criminal Corruption - Dewi, Ratna; Yusuf, Hudi (Journal of Social Research, 2023)
Justice , obstacles and solutions taken when the Restorative justice done . Known barriers _ is obstacle from internal Police in the form of there is a sense of fear and ways long thought , meanwhile from external Police namely the ego sense of the litigants , as well from party government that is No exists issued rules _ about implementation of the Restorative justice . Because deep enforcement priority law _ is a sense of justice Good from the victim as well from party perpetrator , so mediation between party it is very influential big in settlement case . In implementation of Restorative Justice or mediation only can held of the legal process carried out by children as perpetrator ( below age ) with term Diversion, however For case criminal other general yet There is the rules that govern it . The application of restorative justice that can done in situation the that is with carry out mediation between second split the party poured in letter agreement together witnessed by religious leaders or _ figure public as base in implementation title case termination investigation.